Probable impact of age and hypoxia on proliferation and microRNA expression profile of bone marrow-derived human mesenchymal stem cells - Mohd Ali, Norlaily; Boo, Lily; Yeap, Swee Keong; Ky, Huynh; Satharasinghe, Dilan Amila; Liew, Woan Charn; Ong​, Han Kiat; Cheong, Soon Keng; Tunku Zainol Abidin, Tunku Kamarul Zaman (PeerJ, 2016)
Decline in the therapeutic potential of bone marrow-derived mesenchymal stem cells (MSC) is often seen with older donors as compared to young. Although hypoxia is known as an approach to improve the therapeutic potential of MSC in term of cell proliferation and differentiation capacity, its effects on MSC from aged donors have not been well studied. To evaluate the influence of hypoxia on different age groups, MSC from young (< 30 years) and aged (> 60 years) donors were expanded under hypoxic (5% O2) and normal (20% O2) culture conditions. MSC from old donors exhibited a reduction in proliferation rate and differentiation potential together with the accumulation of senescence features compared to that of young donors. However, MSC cultured under hypoxic condition showed enhanced self-renewing and proliferation capacity in both age groups as compared to normal condition. Bioinformatic analysis of the gene ontology (GO) and KEGG pathway under hypoxic culture condition identified hypoxia-inducible miRNAs that were found to target transcriptional activity leading to enhanced cell proliferation, migration as well as decrease in growth arrest and apoptosis through the activation of multiple signaling pathways. Overall, differentially expressed miRNA provided additional information to describe the biological changes of young and aged MSCs expansion under hypoxic culture condition at the molecular level. Based on our findings, the therapeutic potential hierarchy of MSC according to donor's age group and culture conditions can be categorized in the following order: Young (hypoxia) > young (normoxia) > old aged (hypoxia) > old aged (normoxia).